-2x+y=5
x-3y=-30 so you can multiply the bottom equation by 2 you'll get 2x-6y=-60
-2x+y=5
2x-6y=-60 And subtract the equations. You'll get -5y=-55 y=11. Plug it in to one of the original equations. -2x+(11)=5
-2x=-6 so x=3
y=11 and x=3
Answer:
y = -3.84.
Step-by-step explanation:
(0.4y - 3)/(1.5y + 9) = -7/5
Cross multiply:
2y - 15 = -10.5y - 63
12.5y = -48
y = -3.84
Answer:For the first one 26.73 would turn into 27 and 89.42 would stay 89
Step-by-step explanation: Any number that is 5 or greater can be used to round any number.
(-1,-4) this is saying that when x=-1, y=-4. Plugging it into the line equation y=4x gives
![(- 4) = 4( - 1)](https://tex.z-dn.net/?f=%20%28-%204%29%20%3D%204%28%20-%201%29)
Which is correct.
Answer:
f(x)= x^2 - 2, the one in red.
Step-by-step explanation:
To move a quadratic function up/down, you change the value at the very end of the formula.
So instead of f(x)= x^2 + 1, you would do f(x)= x^2 - 2, to move it down 3. This would be the one in red.